The first new chronicle and good government : on the history of the world and the Incas up to 1615 - Guamán Poma de Ayala, Felipe, active 1613 (Joe R. and Teresa Lozano Long series in Latin American and Latino art and culture., 2009)
One of the most fascinating books on pre-Columbian and early colonial Peru was written by a Peruvian Indian named Felipe Guaman Poma de Ayala. This book, The First New Chronicle and Good Government, covers pre-Inca times, various aspects of Inca culture, the Spanish conquest, and colonial times up to around 1615 when the manuscript was finished. Now housed in the Royal Library, Copenhagen, Denmark, and viewable online at www.kb.dk/permalink/2006/poma/info/en/frontpage.htm, the original manuscript has 1,189 pages accompanied by 398 full-page drawings that constitute the most accurate graphic depiction of Inca and colonial Peruvian material culture ever done. Working from the original manuscript and consulting with fellow Quechua- and Spanish-language experts, Roland Hamilton here provides the most complete and authoritative English translation of approximately the first third of The First New Chronicle and Good Government. The sections included in this volume (pages 1?369 of the manuscript) cover the history of Peru from the earliest times and the lives of each of the Inca rulers and their wives, as well as a wealth of information about ordinances, age grades, the calendar, idols, sorcerers, burials, punishments, jails, songs, palaces, roads, storage houses, and government officials. One hundred forty-six of Guaman Poma's detailed illustrations amplify the text.